Navigating in a hierarchy: How middle managers adapt macro design - Marianne Livijn (Journal of Organization Design, 2019)
With the emergence of new organizational forms promoting de-layering, downscoping, and self-management, middle managers have been under attack in recent years. Organizational design has traditionally been concerned with how top management designs organizations, and little is known about the role of middle managers in organizational design. Based on a case study of a reorganization in a leading food production company, this paper contributes to existing research on organizational design by advancing the knowledge of the role of middle managers in organizational design. It contributes to an understanding of organizational design as an iterative process that require active involvement of middle managers in designing micro dimensions of a macro design. In doing so, I provide an extension of prior work, which mainly focuses on vertical interactions and middle managers' efforts to implement the intent of top management. I introduce a new middle manager role, designing, that relies on lateral rather than vertical coordination and interaction. I show how this role creates micro-level organizational elements needed to realize the intent behind top management's strategy and make the macro structural arrangements work. These findings elevate the importance of middle managers in new forms of organizing.
Keywords: 650; Organizational design; Micro design; Macro design; Middle manager strategic influence; Reorganization